The Effect of Economic Factors, Health Conditions, and Access to Education on Social Inequality and Poverty in West Papua - Harsono, Iwan; Sutanto, Himawan; Purwadinata, Subhan; Astuti, Endang; Wafik, Ahmad Zaenal (Westscience Press, 2024)
This research investigates the complex interplay of economic factors, health conditions, and access to education on social inequality and poverty in West Papua through a quantitative analysis. The study, conducted with a sample of 150 participants, employs correlation and regression analyses, supported by SPSS, to unveil significant relationships and dynamics within the socio-economic landscape of the region. Key findings reveal a strong negative correlation between income distribution and poverty rates, emphasizing the pivotal role of economic factors in poverty alleviation. Additionally, a positive correlation between disease prevalence and social inequality underscores the impact of health disparities on socio-economic outcomes. The study also highlights the transformative potential of education, with a robust positive correlation between school enrollment rates and economic well-being. These findings have direct implications for policy formulation, emphasizing the need for integrated approaches that address the synergies and trade-offs among economic, health, and education indicators. The study contributes substantively to the discourse on social inequality and poverty in West Papua, providing empirical evidence to guide evidence-based decision-making.